Brontë e Meyer sob a perspectiva da influência : estudo do diálogo entre as narrativas canônica e trivial através do tempo e da tecnologia, repercutindo no ensino de literatura - Cavalieri, Ana Maria Reino (2015)
The idea that directed the research reported at this thesis was the search for the similarities and differences between deep and surface structures in the canonical and trivial narratives, focusing on the category of the character and having teaching as the ultimate aim. In order to understand the issue, we focused the study on a comparative reading between the Twilight texts by Stephenie Meyer, and The Wuthering Heights by Emily Brontë, bearing in mind the distance in expectations that the works have from each other in many ways, has made it an intriguing object of study and instigated further exploration. With the trivial text as reference we followed the study through a temporal retroactive path looking for links between the Twilight texts and other canonical texts in a way that would allow us to affirm that the first might have been influenced by the latter. Having, therefore, among others, the theoretical support of Flavio Kothe, who has enabled us to observe the boundary position between trivial and canonical texts in some, grounded in the "Ten Commandments" of the trivia from his book Trivial Narrative. From Harold Bloom we got the support tin order to analyze the influence as a guideline for the production of the studied texts, observing how this influence happened over time by direct and indirect means contributing to the feeling of awe conferred to the fans of these texts. We also relied on the contribution of Murray, Iser and Jauss. At the end, we realized that the influence of an artistically elaborated text can be seen in later texts, distant from each other in terms of their classification by critics and disseminated to the public by various ways. We also noted that the knowledge of later texts that allow the perception of his predecessors can assist the reader going to the original text, contributing to a proper pedagogical approach with those who have been initiated in Literature and becoming a facilitator in the literature studies.